2021
DOI: 10.3390/children8040304
|View full text |Cite
|
Sign up to set email alerts
|

Parental Education and the Association between Fruit and Vegetable Consumption and Asthma in Adolescents: The Greek Global Asthma Network (GAN) Study

Abstract: Background: Evidence suggests that nutritional factors, such as consumption of fruits and vegetables, along with socioeconomic factors such as parental education level, are associated with asthma prevalence. Our study examined the role of parental education in the association between fruit and vegetable consumption and adolescent asthma. Methods: 1934 adolescents (mean age: 12.7 years, standard deviation: 0.6 years, boys: 47.5%) and their parents were voluntarily enrolled and completed a validated questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…A striking finding in our study was that approximately 25% of our FPIAP infants had parents with higher education compared with 60% of HC infants. In the Mediterranean area, parental tertiary education has been found associated with high consumption of fruits and vegetables, and low childhood asthma prevalence ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…A striking finding in our study was that approximately 25% of our FPIAP infants had parents with higher education compared with 60% of HC infants. In the Mediterranean area, parental tertiary education has been found associated with high consumption of fruits and vegetables, and low childhood asthma prevalence ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Table S3 shows the baseline characteristics of the cohort and cross-sectional studies recorded separately in this meta-analysis, while Table S4 presents the specific statistical values in each article. In total, 63 articles were included for data analysis, due to the inclusion of the same population in the four articles by Arvaniti et al 57 , 58 and Antonogeorgos et al 86 , 87 …”
Section: Resultsmentioning
confidence: 99%
“…Karatas and colleagues reported that a higher maternal educational level was associated with an increased risk of FPIAP [ 53 ]. There is documentation of an association between lower parenteral education and socioeconomic status, with a poorer quality of diet and an increased risk of asthma, along with low adherence to asthma medication use being observed [ 54 ]. In our, study, once FPIAP was diagnosed, a higher maternal educational level was associated with earlier resolution of symptoms, as group A mothers more often had a higher level of education.…”
Section: Discussionmentioning
confidence: 99%